Effect of Dry Aging on Beef Muscle Proteins - Galina V. Gurinovich; Irina S. Patrakova; Vladislav A. Khrenov; Marina V. Patshina; Antonina I. Shevchenko (Техника и технология пищевых производств)
Meat is an inherent part of human diet. Its quality develops at different stages of production, storage, and processing. In this respect, the stage of aging is especially important. This technology makes it possible to regulate biochemical processes in meat raw materials. Long-term dry aging is a promising method that presupposes conditions that limit the growth of microorganisms. The transformations in the protein component are an important but understudied aspect of meat quality formation during dry aging. The research featured Hereford beef carcasses of Siberian breeding. The samples were isolated from the inner part of bone spinal-lumbar cuts after 21, 35, and 42 days of dry aging under the following conditions: 0–1°C, 74–75% relative humidity, 0.5 m/s air velocity. The samples were subjected to dry aging after 24 h at 4°C. The fractional composition of proteins was controlled by vertical electrophoresis in a Mini-Protean Tetra System chamber. The amino acid composition was defined by high-performance liquid chromatography in a Shimadzu LC-20 Prominence liquid chromatograph with a Shimadzu SPD20MA diode-matrix detector and a Kromasil C-18 separation column. The protein digestibility was measured by sequential exposure to pepsin-trypsin proteinase system under simulated gastric digestion. Long-time dry aging triggered proteolysis under the action of endogenous enzymes. The electropherogram analysis showed that the proteolytic changes in high-molecular myofibrillar proteins of high-quality beef became more pronounced after a longer maturation period. The distribution of protein fractions by dry aging stages indicated a different rate of degradation of contractile, regulatory, and cytoskeletal proteins. As a result, the structural integrity of muscle fibers degraded, the meat grew tender, and the proteins became more available to digestive enzymes. The amino acid and protein digestibility analyses in vitro demonstrated an increase in the nutritional value of beef and the availability of proteins to the action of proteinases after 42 days of dry aging. Long-term dry aging of high-quality beef increased the digestibility of muscle proteins as a result of proteolysis that accompanied the accumulation of low-molecular fractions. According to the amino acid analysis, the optimal result was most pronounced on day 42 as proven by the moderate oxidative changes in proteins.